ENHANCING ENGLISH LANGUAGE LEARNING AMONG ESL STUDENTS THROUGH PAIR WORK: A PRACTICAL CLASSROOM APPROACH - Sidikova Gulbakhor (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
ABSTRACT: Pair work has become one of the most effective interactive strategies in teaching English to ESL students. It encourages communication, increases student participation, and helps learners develop autonomy while practicing authentic language use. This paper examines the major benefits of pair work, supported by theoretical perspectives and practical classroom observations. Key advantages include improved speaking fluency, reduced learner anxiety, and the ability to practice target structures in meaningful contexts. The article also outlines methodological recommendations for implementing pair work effectively, including clear task design, role distribution, and monitoring techniques. The findings demonstrate that pair work significantly enhances students’ confidence, accuracy, and collaboration skills. The paper concludes by emphasizing the importance of interactive methods in modern ESL classrooms and recommends integrating pair work as a core component of daily instruction.